Public transport inventory monitoring system for developing countries - Muperi, Custen Simbarashe (Midlands State University, 2020)
This report serves to give an account for a research on a Public Transport Inventory Monitoring System for Developing Countries. The research is based on the current situation in Zimbabwe where the public transport industry is dominated by the informal sector. In this document there is a discussion of the transport industry in Zimbabwe, identification of the problem of accountability of inventory in the current industry, a methodology to help solve the problem and the results of using the method discussed.